If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -6) + 6 = 6(x + 2) + -4 Reorder the terms: 4(-6 + x) + 6 = 6(x + 2) + -4 (-6 * 4 + x * 4) + 6 = 6(x + 2) + -4 (-24 + 4x) + 6 = 6(x + 2) + -4 Reorder the terms: -24 + 6 + 4x = 6(x + 2) + -4 Combine like terms: -24 + 6 = -18 -18 + 4x = 6(x + 2) + -4 Reorder the terms: -18 + 4x = 6(2 + x) + -4 -18 + 4x = (2 * 6 + x * 6) + -4 -18 + 4x = (12 + 6x) + -4 Reorder the terms: -18 + 4x = 12 + -4 + 6x Combine like terms: 12 + -4 = 8 -18 + 4x = 8 + 6x Solving -18 + 4x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -18 + 4x + -6x = 8 + 6x + -6x Combine like terms: 4x + -6x = -2x -18 + -2x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 -18 + -2x = 8 + 0 -18 + -2x = 8 Add '18' to each side of the equation. -18 + 18 + -2x = 8 + 18 Combine like terms: -18 + 18 = 0 0 + -2x = 8 + 18 -2x = 8 + 18 Combine like terms: 8 + 18 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
| 0=-2x^2+4x+4 | | -c+3.4=6.21 | | -2.1m=8.4 | | 9-2x=7+2x-6 | | 10=2(y-4)+4 | | 56=c+24 | | -8(4b+3)+(33b-7)=0 | | 7x-9=3(x+5) | | 1.3x-2.39=5.67x+4.74 | | b+5=-10 | | .75a-.666=.583 | | 3(4-5k)-5(7-2k)+6=3k+7 | | .3333333334z-4=-.3333333334z+18 | | z^2+9z-9=(2z+3)(z-3) | | 2v^3-3v^2-14v+21=0 | | 6(x-3)=2x+4-6 | | 4-49v^2=0 | | -3/4+(-3/4)=0 | | -6x+16=-2x | | .5d=2-.5d | | 2/5+1/5=0 | | 4.8q-5.9-5.7q=-1.9q-4.2 | | 1.3p+0.3p-2=1.2 | | 15a^2+a=2 | | 4(4x-5)= | | 9x^2+15x+52=352 | | 2x^2+3y^2-2xy=10 | | 7y^2+23y=20 | | 8(2+x)=3x-14 | | 108-2x=34x+20 | | 3(z-7)=18 | | 30v^3x^9+9v^2x^6y^4=0 |